Trajectories of social justice within social stratification: towards a Bourdieusian reading of social class for social workers - Flynn, Susan (My University, 2022)
Social class refers to hierarchal social stratification of society, which, from a Bourdieusian theoretical lens, can be enacted across social, cultural, economic and symbolic lines (Bourdieu, 1977; Waquant, 2006). For social workers, social class jeopardises and undermines social justice (Feldman & Shdaimah, 2012), and yet, it endures unabated as a contrary condition to just and egalitarian societies. Toward a more concise and theoretically informed understanding of social class and social justice, this paper presents selected social stratification, social prestige and socio-economic status scales that have garnered significant influence in the social sciences. These are then critically considered through a bespoke conceptual frame, entailing Bourdieusian theory of capital, extended and applied within Bonnycastle’s Relational Illustrative Model (2011). The overall aim of the paper, in this context, is to assist social workers in understanding and therefore contesting social class inequality, toward a more egalitarian and socially just society. The paper is structured in the following way. First, rationale for drawing upon Bonnycastle’s (2011) and Bourdieu’s (1977) work are teased out. Thereafter, Bourdieu’s theory of capital is introduced in more depth and explained, followed by engagement with established limitations of Bourdieusian theory for social work and social class. After this, selected social stratification scales are presented with a view to developing an evidence informed stance on social class. To then move toward a more socially just interrogation of social class within social work practice and academia, five “interconnected and mutually supportive categories” of social justice derived from the Relational Illustrative Model (Bonnycastle, 2011, p.272), are used to structure concluding discussion. These refer respectively, to distributive justice, identity, human rights, social welfare and political ideology. Overall, the intention is to be practically helpful, for social work students, practitioners and allies, pursuing a more egalitarian and classless society, however ambitious that may be.
PUBLISHED